Transforming social capital into performance via entrepreneurial orientation. Issue 4 (November 2020) - Nguyen, Long Thanh; An, Jake; Ngo, Liem Viet; Hau, Le Nguyen
Highlights: External network ties and social interaction generate greater relationship quality. Proactiveness mediates the effect of relationship quality on firm performance. Innovativeness and risk taking do not mediate the effect of relationship quality on firm performance. Abstract: Despite the importance of social capital (e.g. external network ties, social interaction, and relationship quality) and entrepreneurial orientation (e.g. proactiveness, innovativeness, and risk taking) for firm performance, little is known about the mechanisms that benefit firms from the interplay among these factors. It has also been unclear which entrepreneurial processes or activities assist in transforming social capital into positive performance outcomes. In this study, we clarify how and why entrepreneurial orientation assists in transforming social capital into firm performance. A survey of 198 entrepreneurs in Vietnam shows that entrepreneurial firms need both bridging and bonding capital (i.e. external network ties and social interaction) for enhanced relationship quality. While proactiveness mediates the impact of relationship quality on firm performance, findings show no support for the mediating role of innovativeness and risk taking. In other words, proactiveness converts relationship quality into enhanced firm performance, while innovativeness and risk taking do not. Chinese Abstract: 尽管社会资本 (如外部网络联系, 社会互动和关系质量) 和创业导向 (如主动性, 创新性和风险承担) 对企业绩效很重要, 但这些因素之间的相互作用对企业的收益机制知之甚少. 目前也不清楚哪些创业程序或活动有助于将社会资本转化为积极的业绩成果. 在本研究中, 我们阐明了创业导向如何以及为什么有助于将社会资本转化为企业绩效. 一项对198名越南企业家的调查显示, 创业企业需要桥梁和纽带资本 (即外部网络联系和社会互动) 来提高关系质量. 虽然主动性介导了关系质量对企业绩效的影响, 但研究结果并不支持创新性和风险承担的中介作用. 换句话说, 主动性将关系质量转化为增强的企业绩效, 而创新性和冒险性则不然.